2020
DOI: 10.5116/ijme.5e3e.7f16
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement, job satisfaction, and turnover intentions among family medicine residency program managers

Abstract: Objective:The authors examined the associations between work engagement, job satisfaction, and turnover intentions among family medicine residency (FMR) managers. Methods: We conducted a cross-sectional online survey of 511 FMR manager members of the Association of Family Medicine Administration using purposive sampling. The Utrecht Work Engagement Scale, Job Satisfaction Survey, and Boshoff and Allen's 3-item scale were used to assess work engagement, job satisfaction, and turnover intentions respectively. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
4
13
0
1
Order By: Relevance
“…In the present study, job satisfaction was found to be the most significant variable with respect to WE, which is consistent with previous studies [37,38]. Job satisfaction is under-stood as the feeling of satisfaction and pleasure provided by work, which can positively affect people's lives [37]. Therefore, it is to be expected that people who enjoy their work activity with pleasure are more committed to their work; furthermore, this relationship could be explained by the job demands-resources model.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, job satisfaction was found to be the most significant variable with respect to WE, which is consistent with previous studies [37,38]. Job satisfaction is under-stood as the feeling of satisfaction and pleasure provided by work, which can positively affect people's lives [37]. Therefore, it is to be expected that people who enjoy their work activity with pleasure are more committed to their work; furthermore, this relationship could be explained by the job demands-resources model.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies showed that employees with more elevated work engagement levels had less level of dissatisfaction and higher levels of performance (Leijten et al, 2015;Shimazu et al, 2016). Work engagement has also been related to job satisfaction and turnover intention (Ofei-Dodoo et al, 2020).…”
Section: Work Engagement As Mediatormentioning
confidence: 97%
“…Engagement is one of the emerging concepts of positive psychology that is characterized by motivation, enthusiasm, and commitment at work 8 . Work engagement is defined as a positive, fulfilling, work-related state of mind that is characterized by vigor, dedication, and absorption 1,4,7,10,12 . Vigor is characterized by high levels of energy and mental resilience while working, a willingness to invest in work, and persistence in difficult situations.…”
Section: Engagementmentioning
confidence: 99%
“…Engagement also offers a competitive advantage to the organizations in which individuals work 1,8 . The possible consequences of work engagement are described as positive attitudes toward the organization, such as having initiative and motivation to learn 7 , a willingness to work overtime 7 , proactive behavior 7 , higher productivity 12 , increased organizational commitment 7 , and low turnover 7,12 . Work engagement is positively related to work performance 7,13 and is also associated with low levels of depression, stress, and psychosomatic complaints 7 .…”
Section: Engagementmentioning
confidence: 99%
See 1 more Smart Citation